2003
DOI: 10.1097/01.ta.0000047805.89700.c1
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of Posttraumatic Pulmonary Embolism: Is Chest Computed Tomographic Angiography Acceptable?

Abstract: PE frequently occurs soon after injury. The majority of PEs after trauma are found peripherally (in segmental or subsegmental vessels). Right/left pulmonary artery embolisms are likely to be found only later in a trauma patient's course. Any diagnostic study used to diagnose pulmonary embolism in trauma patients must have sufficient resolution capacity to reliably detect segmental and subsegmental clot. A diagnostic modality such as CT scanning that is insensitive to peripheral embolisms may miss a significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
5
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 21 publications
1
5
0
Order By: Relevance
“…In contrast to other populations, the authors have noted that PE occurs early after injury. In a subsequent study, 16 they have confirmed that more than one fourth of the patients had a PE within the first 4 days after admission. Furthermore, they found that three fourths of their patients had PE confined to peripheral vessels.…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…In contrast to other populations, the authors have noted that PE occurs early after injury. In a subsequent study, 16 they have confirmed that more than one fourth of the patients had a PE within the first 4 days after admission. Furthermore, they found that three fourths of their patients had PE confined to peripheral vessels.…”
Section: Discussionsupporting
confidence: 58%
“…Under these conditions, the lack of sensitivity of CTPA to detect peripheral emboli is concerning. The incidence of peripheral PE was 5% in studies with predominantly medical populations 11,17 and over 50% (a 10-fold increase) in studies with predominantly surgical populations 15,16 and in our study. Decreasing the collimation from 3 mm to 2 mm or 1 mm improved the identification of peripheral vessels.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…The prevention, diagnosis, and treatment of PE remain unsettled in trauma. Methods of prevention are ineffective, 22 methods of diagnosis potentially inaccurate, 1,7 and methods of treatment debated. 23 In particular, severely injured patients confuse the picture even further by the multiple confounding factors that complicate their clinical presentation and outcome.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4] Although it has been used successfully in predominantly medical patients, 2-6 the published evidence on its accuracy when used in critically injured patients is far from convincing. 1,7 Transport out of the intensive care unit, even if of shorter duration than for conventional pulmonary angiography, remains a problem with CT. 8,9 Venous ultrasonography and measurement of Ddimer levels have been used as alternative methods to diagnose PE without subjecting the critically injured patient to the risks of transport. Although normal Ddimer levels carry a very high negative predictive value for PE after the 4th day of trauma, 10,11 they are unreliable in earlier periods during which a significant number of thromboembolic events occurs.…”
mentioning
confidence: 99%